2017
DOI: 10.2166/wh.2017.189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacterial community in shower water before and after chlorination

Abstract: Bathers release bacteria in swimming pool water, but little is known about the fate of these bacteria and potential risks they might cause. Therefore, shower water was characterized and subjected to chlorination to identify the more chlorine-resistant bacteria that might survive in a chlorinated swimming pool and therefore could form a potential health risk. The total community before and after chlorination (1 mg Cl L for 30 s) was characterized. More than 99% of the bacteria in the shower water were Gram-nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this study, the level of free chlorine in the pool water set by the regulations (1-3 mg/L) was met in 70% of establishments. The international, newly issued regulations target SARS-CoV-2 inactivation in 15-30 s in the pool water, with the level of chlorination and pH values being of primary concern [27][28][29][30]. Most countries increased the levels of chlorination in pool waters, although there are concerns about the possible ecological consequences that may be associated with such a practice and the possible impact on human health [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the level of free chlorine in the pool water set by the regulations (1-3 mg/L) was met in 70% of establishments. The international, newly issued regulations target SARS-CoV-2 inactivation in 15-30 s in the pool water, with the level of chlorination and pH values being of primary concern [27][28][29][30]. Most countries increased the levels of chlorination in pool waters, although there are concerns about the possible ecological consequences that may be associated with such a practice and the possible impact on human health [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the analysis methods are easier to apply and low-cost. These potential pathogens enter the pool (for instance by vomiting, saliva, mucus, and sweat), so there is a contingent health risk [22].…”
Section: Discussionmentioning
confidence: 99%
“…Demographics with 13 questions: (1) gender, (2) age, (3) height, (4) body weight, (5) place of residence, (6) citizenship, (7) swimming pool, (8) father's age, (9) mother's age, (10) family income, (11,12) parents' educational level, (13) frequency of use of a swimming pool in the given period (Figure 1). Treatment, recovery, and effects on daily activities with 8 questions: (20) treatment for otitis externa, (21) what treatment, (22) if use of the pool was discontinued, (23) consulted physician, (24) public or private physician, (25) response to treatment, (26) recovery time, (27) abstinence from normal obligations.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations, performed due to the deterioration of the Palaeolithic paintings of Lascaux Cave (France), revealed that the cave was a reservoir of potential pathogenic protozoa and bacteria such as Ralstonia, Pseudomonas, Legionella, Achromobacter, Bordetella, Shigella or E. coli, previously linked to outbreaks related to air-conditioning systems and cooling towers in community hospitals and public buildings (Bastian et al 2009). The use of designated 'indicator organisms' such as Enterobacteriaceae (Peters et al 2018), E. coli (Anderson et al 2005) or coliform bacteria (Shakoor et al 2018) can detect human induced disturbances, as well as faecal associated contamination (Lavoie and Northup 2006). It was found that bacterial abundance varies greatly at different sampling times, as shown by Wang et al (2010; in four different sites in the Mogao Grottoes (China).…”
Section: Introductionmentioning
confidence: 99%